2022
DOI: 10.1093/jac/dkac254
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 and TLR4 activity in monocytes and macrophages after exposure to amoxicillin, ciprofloxacin, doxycycline and erythromycin

Abstract: Background Antibiotics are used to treat bacterial infections but also impact immunity. This is usually attributed to antibiotic-induced dysbiosis of the microbiota, but antibiotics may have a direct effect on immune cells and immunity-associated receptors, such as Toll-like receptors (TLRs). Objectives To investigate whether antibiotics alter TLR2/1, TLR2/6 and TLR4 activity in immune cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It is also possible that antibiotics have direct effects on immune cells and immune-mediated receptors that can modify risk for NEC ( 97 , 98 ). For example, in vitro studies revealed that gentamicin, a first-line antibiotic drug of choice for neonatal sepsis, can directly inhibit the chemotactic response of human polymorphonuclear leukocytes ( 99 ).…”
Section: Additional Speculations From Human and Animal Studiesmentioning
confidence: 99%
“…It is also possible that antibiotics have direct effects on immune cells and immune-mediated receptors that can modify risk for NEC ( 97 , 98 ). For example, in vitro studies revealed that gentamicin, a first-line antibiotic drug of choice for neonatal sepsis, can directly inhibit the chemotactic response of human polymorphonuclear leukocytes ( 99 ).…”
Section: Additional Speculations From Human and Animal Studiesmentioning
confidence: 99%
“…However, when we examined it from the same perspective, EM982 showed immunomodulatory activity toward all cell lines used in this study, whereas EM decreased cytokine production only in PMA-untreated THP-1 cells. Three previous studies have reported the effect of EM on cytokine production in THP-1 cells: EM inhibited IL6 transcription in PMA-untreated THP-1 cells by approximately 20% at the mRNA level ( 24 ), EM had no significant effect on TNF-α and IL-6 production in PMA-differentiated THP-1 cells at the protein level ( 25 ), and EM decreased IL-8 production in THP-1 cells differentiated with 1,25-dihydroxy vitamin D3 by approximately 60% at the protein level ( 26 ). These findings suggest that the effect of EM differs depending on the differentiation method even in the same cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various PRRs in macrophages, TLRs play a pivotal role in the recognition of foreign pathogens ( 38 ). TLR2 and TLR4 play crucial roles in the elimination of foreign pathogens by inducing the production of proinflammatory mediators and activating phagocytic activity in macrophages ( 40 ). In the present study, it was observed that inhibition of TLR4 in cells resulted in a significant decrease in CF-mediated pro-inflammatory mediator production and phagocytic activation compared with cells with inhibition of TLR2.…”
Section: Discussionmentioning
confidence: 99%